Translation Analysis of Idiomatic Expression Found In “Zootopia” Movie - Syawal, Syawaliyah Putri Andini; Hilman, Evert Haryanto; Agustina, Maftuchah Dwi (IdeBahasa, 2023)
This research used the data source "Zootopia" (2016). The researcher analyzed the translation strategies of idiomatic expressions using semantic strategies and syntactic strategies also evaluates the quality of the translation. This study uses the theory of translation strategies by Chesterman and analyzed the quality of translation by translator using the theory of Nababan, Nuraeni & Sumardiono (2012), another theory based on Newmark for supporting theory in this research. This research method used by descriptive qualitative. The dominant data points obtained from this study were from syntactic strategies, namely unit shift with 14 data points and dominant semantics, namely paraphrasing with 16 data points. The results of this research showed that there were 100 data which contain types of translation strategies applied in idiomatic expressions, consits are; syntactic strategies with unit shift 14 data (14%), semantic strategies with paraphrase 16 data (16%), and semantic strategies trope change 5 data (5%). The quality of the translation used by the translator has accumulated data analysis. they are: high accuracy data, high acceptability data, and high readability data.